Postsynaptic plasticity of GABAergic synapses. (1st June 2020) - Barberis, Andrea
Abstract: The flexibility of neuronal networks is believed to rely mainly on the plasticity of excitatory synapses. However, like their excitatory counterparts, inhibitory synapses also undergo several forms of synaptic plasticity. This review examines recent advances in the understanding of the molecular mechanisms leading to postsynaptic GABAergic plasticity. Specifically, modulation of GABAA receptor (GABAAR) number at postsynaptic sites plays a key role, with the interaction of GABAARs with the scaffold protein gephyrin and other postsynaptic scaffold/regulatory proteins having particular importance. Our understanding of these molecular interactions are progressing, based on recent insights into the processes of GABAAR lateral diffusion, gephyrin dynamics, and gephyrin nanoscale organization. This article is part of the special issue entitled 'Mobility and trafficking of neuronal membrane proteins'. Highlights: Mechanisms of postsynaptic plasticity at GABAergic synapses. Role of GABAA receptors lateral diffusion in the expression of postsynaptic GABAergic synaptic plasticity. Modifications of GABAergic postsynaptic nanoscale organization during GABAergic synaptic plasticity. Open question and future directions.